Responses of photosynthesis to high temperatures in oak saplings assessed by chlorophyll-a fluorescence: inter-specific diversity and temperature-induced plasticity - Daas, C; Montpied, P; Hanchi, B; Dreyer, E (Annals of forest science, 2008)
• The sensitivity of photosynthesis to high temperature was investigated in greenhouse-grown saplings of three Mediterranean (Quercus canariensis Willd., Q. coccifera L. and Q. suber L.) and two temperate European oak species (Q. robur L. and Q. petraea Matt. Liebl.). The sensitivity to high temperature was inferred from F0T curves producing the critical temperature (Tc ) at which a rapid rise in ground chlorophyll a ﬂuorescence (F0) occurs. Tc is known to acclimate to moderately increased ambient temperature by displaying signiﬁcant increases. • We ﬁrst checked whether acclimation of Tc was paralleled by an increase in optimal temperature for light driven electron ﬂux (Topt ,), recorded by measuring quantum yield of photochemistry under saturating CO2 and moderate irradiance. Saplings of Q. suber and Q. canariensis were submitted to four, ﬁve days long ambient temperature steps (15, 25, 35 and 15 ◦ C again). Tc was usually largely above 45 ◦ C while Topt was around 30–35 ◦ C. Both increased with ambient temperature in the two species, and decreased again when temperature returned to the initial values. This recovery was nevertheless not complete after a week at 15 ◦ C. • A second experiment tested whether the plasticity of Tc was of the same extent in the ﬁve species. A signiﬁcant increase of Tc followed by a decrease was detected in all species. Only small inter-speciﬁc diﬀerences were detected in Tc , and temperature induced plasticity was similar in the diﬀerent species: Tc increased by about 4–5 ◦ C while ambient temperature was increased from 15 to 35 ◦ C. Mediterranean and European oaks did not diﬀer in this respect. • This result does not support the hypothesis that oak species from warmer regions would display a larger plasticity of Tc in response to increasing temperatures.
Keywords: optimal temperature; Photochemistry; quantum yield; Quercus canariensis; Quercus coccifera; Quercus petraea; Quercus robur; Quercus suber